Kloning gen penyandi β-1,6-glukanase kapang secara cepat dengan teknik RT-PCR menggunakan primer spesifik Rapid cloning for gene encoding fungal β-1,6-glucanase by means of RT-PCR using specific primers - Asmini BUDIANI; Riza A. PUTRANTO; Hayati MINARSIH; Niyyah FITRANTI; Djoko SANTOSO (E-Journal Menara Perkebunan, 2009)
AbstractProduction of bioethanol from biomass ofagricultural waste has been hindered with a highproduction cost because enzymes needed for theprocess has to be imported with relatively a highprice. Genetic engineering using its encodinggenes is able to produce those enzymes withlower cost. In this report we described a researchaimed to clone gene encoding β-1,6-glucanasefrom Trichoderma harzianum with a relativelyrapid and inexpensive method, by means of RT-PCR using gene specific primers. The primerswere designed based on the DNA sequence of thetarget gene from the same species of organismused in this research. RT-PCR using that primersresulted in DNA fragment with sizescorresponding to the predicted size of full lengthgene encoding β-1,6-glucanase, about 1300 bp.After a sequential experiments of cloning usingpGEM-T Easy vector, DNA sequencing andBlastN - BlastX analyses of the sequences, it wasproven that the isolated DNA was full length geneof β-1,6-glucanase. This was implied from thepercentage of Identity and E-value which were96% and 0.0 (< e-04) respectivety.AbstrakProduksi bioetanol dari biomassa limbahpertanian, terkendala oleh tingginya biayaproduksi karena enzim yang diperlukan untukproses tersebut masih harus diimpor denganharga yang relatif mahal. Melalui rekayasagenetika menggunakan gen-gen penyandinya,enzim-enzim tersebut dapat diproduksi denganbiaya yang lebih murah. Penelitian ini bertujuanuntuk mengklon gen penyandi β-1,6-glukanasedari Trichoderma harzianum secara cepat danekonomis, dengan RT-PCR menggunakan primerspesifik. Primer tersebut dirancang berdasarkansekuen DNA dari gen target asal spesiesorganisme yang sama dengan yang digunakandalam penelitian. RT-PCR dengan primertersebut menghasilkan fragmen DNA yangukurannya sesuai dengan gen lengkap penyandiβ-1,6-glukanase, yaitu sekitar 1300 bp. Setelahsecara berurutan diklon menggunakan vektorpGEM-T Easy, sekuensing urutan DNA dananalisis BlastN maupun BlastX dari sekuen yangdiperoleh, terbukti bahwa fragmen DNA tersebutadalah gen lengkap penyandi β-1,6-glukanase.Hal ini ditunjukkan oleh Nilai Kesamaan(Identity) dan E-Value yang masing-masingmencapai 96% dan 0.0.